2022
DOI: 10.1111/nph.18445
|View full text |Cite
|
Sign up to set email alerts
|

The formation of stipule requires the coordinated actions of the legume orthologs of Arabidopsis BLADE‐ON‐PETIOLE and LEAFY

Abstract: Stipule morphology is a classical botanical key character used in plant identification. Stipules are considerably diverse in size, function and architecture, such as leaf-like stipules, spines or tendrils. However, the molecular mechanism that regulates stipule identity remains largely unknown.We isolated mutants with abnormal stipules. The mutated gene encodes the NODULE ROOT1 (MtNOOT1), which is the ortholog of BLADE-ON-PETIOLE (BOP) in Medicago truncatula. We also obtained mutants of MtNOOT2, the homolog of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…From the above process, it was found that the differentiation of G. koreanum inflorescences started from the differentiation of stipular and leaf primordia. Stipules are considered as outgrowths or appendages at the base of petioles, growing in an orderly manner on the stem nodes of flowering plants [ 24 ]. The research on the stipules had a long tradition, and there were rich achievements in the research on the origin of stipules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the above process, it was found that the differentiation of G. koreanum inflorescences started from the differentiation of stipular and leaf primordia. Stipules are considered as outgrowths or appendages at the base of petioles, growing in an orderly manner on the stem nodes of flowering plants [ 24 ]. The research on the stipules had a long tradition, and there were rich achievements in the research on the origin of stipules.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some scholars believed that Dicotyledon stipules and Monocotyledon leaf tongues had different development origins [ 25 ]. A systematic study of stipules and colleters of mangrove Rhizophoraceae showed that the morphology correlated with the shape of their colleter aggregations [ 26 ]; the presence of stipules in the outer organs of apetala2-1 flowers was evidence of their leaf-like structure [ 27 , 28 ]; and other studies were related to the formation and evolution of stipules [ 24 , 29 ]. In our observation, the apical meristem of G. koreanum first formed a circle of divisions around its periphery, while differentiating into stipule and leaf primordia.…”
Section: Discussionmentioning
confidence: 99%
“…SEM was performed as described previously ( Zhang et al., 2022 ). Briefly, leaves were fixed, dehydrated, critical point dried, and observed for imaging.…”
Section: Methodsmentioning
confidence: 99%